Perfil dos pacientes com linfoma e HIV em 5 centros da cidade de São Paulo: um estudo retrospectivo - Vargas, Juliano Cordova [UNIFESP] (2021)
Introduction: Cancer is the leading cause of death in HIV patients in economically developed countries, even in the era of antiretroviral therapy (ART). The main cause of death in patients with HIV/AIDS, regarding the neoplastic etiology, are lymphomas. In the United States, non-Hodgkin's lymphomas are the most common cancer. Objectives: To describe the profile of patients with HIV/AIDS and who are diagnosed with concomitant lymphoproliferative diseases, in the 5 centers mentioned in this work; as well as: Assess the incidence of immune reconstitution lymphoma and identify prognostic factors for lymphoproliferative diseases and predict their respective interference in survival rates. Patients and Methods: Patients were recruited from Hospital São Paulo/UNIFESP (HSP), Instituto Emílio Ribas (IIER), Hospital Israelita Albert Einstein (HIAE), Instituto do Câncer de São Paulo (ICESP)/HC from FMUSP and Centro Paulista de Oncology (CPO), in the period from January 2000 to January 2019. Demographic data, clinical and epidemiological characteristics, laboratory tests, in addition to staging tests were obtained from patients with a confirmed anatomopathological diagnosis of Hodgkin's or non-Hodgkin's lymphoma and with a confirmed HIV diagnosis. Results Ages ranged from 17 to 79 years, with a median of 42 years, 205 (74.3%) were male and 71 (25.7%) were female. 79 (28.6%) had ECOG 0, 128 (46.4%) had ECOG 1, 38 (13.8%) had ECOG 2, 13 (4.7%) had ECOG 3, eight (2.9% ) with ECOG 4. The lymphomas were mostly of the non-Hodgkin type, present in 246 (89.2%) patients, followed by 26 (9.4%) patients with Hodgkin's Lymphoma and three (1.1%) patients with Castelman's disease. We observed that 40 (14.5%) had infiltrated bone marrow. At the time of HIV diagnosis, 93 (38.9%) patients had an undetectable viral load and 146 (61.1%) had a detectable viral load. The CD4 countgreater than 200 occurred in 117 (47%) patients, and less than 200 in 132 (53%) patients. 172 patients (63.7%) were using antiretroviral therapy. 160 (41.4%) patients had normal LDH and 150 (58.6%) had abnormal LDH. The beta 2 microglobulin, monocyte count, lymphocyte and lymphocyte-monocyte ratio had their medians estimated at 3.2, 500, 1198 and 2.5 respectively. Together, ECOG and lymphoma relapse/recurrence statistically influenced patient survival (p < 0.05), with the mortality risk of the patient with ECOG (3/4) being 2.68 times the risk of the patient with ECOG (0/1/2) and patients who experienced relapse/relapse had a mortality risk 2.15 times the risk of patients who did not experience relapse/relapse. Immune Reconstitution Lymphoma (IRI) had an incidence of 9.8%. Conclusions: In the present study, we observed a predominance of male patients, with a median age of 42 years, satisfactory ECOG, 83.7% with stage III/IV and non-Hodgkin's lymphomas. The status of the HIV virus, the CD4 lymphocyte count influenced the survival of the evaluated patients and reinforce that adequate control of the virus implies better clinical outcomes. Relapse and relapse, together, influenced patient survival. The use of rituximab does not seem to have had an impact on the response outcomes of this cohort of patients with lymphoma and HIV.